Acidic soil, Environmental extent, and different strategies of reclamation– A Review - Selva Raja Pushpa. A; Kalidass Subramaniam (The Bioscan, 2025)
Soil is a crucial ingredient in the creation of agricultural goods. The production of this soil diminishes whenever it loses its fertility, regardless of whether the cause is acidity or alkalinity. This review focuses on the issues crops face due to soil acidity. The soil's acidity represents the most significant challenge confronting the worldwide food producing business. Acidic soil can occur in every geographical region worldwide. This review primarily examines global regions characterized by acidic soils. This page extensively discusses the chemical and biological approaches for reclaiming acid soils, accompanied by various examples and case studies.